Modular assembly and immunological evaluation of a promising bioconjugate nanovaccine against Klebsiella pneumoniae O2 serotype - Peng Sun; Chao Pan; Huifang Xu; Bo Liu; Jingqin Ye; Kangfeng Wang; Yan Zhang; Ting Li; Li Zhu; Yating Wang; Hengliang Wang; Jun Wu (npj Vaccines)
Abstract The antimicrobial-resistant (AMR) Klebsiella pneumoniae (Kp) poses an enormous threat to human health, with O2 serotypes accounting for up to 35–59% of infections. Although the O-polysaccharide (OPS) of the Kp O2 serotype can be used as an antigen target for vaccine preparation, its simple structure (only galactose repeats) makes it difficult to generate effective antibody responses and protection. Here, we prepared a novel Kp O2 OPS bioconjugate nanovaccine using protein glycan coupling technology (PGCT) and a SpyCatcher/SpyTag (SC/ST) orthogonal assembly system. The hepatitis B virus core antigen (HBc), which can assemble into nanoparticles, was used as a carrier to display OPS on its surface, allowing the bioconjugate to reach the nanoscale. The HBc-OPS exhibited attractive stability without aggregation or degradation for up to 10 months. A series of mouse experiments revealed the OPS-specific antibody activation ability of HBc-OPS and its protective effect against different infection doses. In particular, when coadministered with the AS03 adjuvant, all the mice were protected from higher doses of lethal attacks. Through in vitro and in vivo experiments, we found that the addition of AS03 further promoted the humoral immune response by stimulating increased levels of cytokines and T follicular helper (Tfh), germinal center B (GC B), and antigen-specific memory B cells. Moreover, we found that the use of AS03 as an adjuvant can provide a better protective effect than commonly used CpG-based adjuvants. Therefore, we have developed an attractive, stable, and effective bioconjugate nanovaccine against the Klebsiella pneumoniae O2 serotype. This bioconjugate nanovaccine design greatly potentiated the immunogenicity of polysaccharides, and the orthogonal modular assembly strategy reduced the technical difficulty of bioconjugate nanovaccine preparation, both of which could be applicable to the development of OPS conjugate vaccines for serotypes with low immunogenicity.